2015
DOI: 10.1074/jbc.m115.670976
|View full text |Cite
|
Sign up to set email alerts
|

PAX3 and FOXD3 Promote CXCR4 Expression in Melanoma

Abstract: Background: CXCR4 promotes melanoma metastasis. Results: FOXD3 and PAX3 drive CXCR4 expression. Blocking these factors inhibits cell migration, but this is rescued by ectopic CXCR4 expression. Conclusion: PAX3-and FOXD3-mediated melanoma cell migration is dependent on promoting the expression of CXCR4. Significance: This study identifies a new pathway and targets for therapeutic strategies to treat invasive melanoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 53 publications
0
22
0
Order By: Relevance
“…De novo assembly and analysis of the foxd3 -mutant transcriptomes revealed the presence of truncated foxd3 fluorescent fusion transcripts (Figure S3A), encoding only 93 N-terminal amino acids, as shown previously (Hochgreb-Hägele and Bronner, 2013). The truncated N-terminal foxd3 variants are non-functional (Yaklichkin et al., 2007), whereas dominant negative activity is associated with the C terminus regions (Kubic et al., 2015, Zhu et al., 2014). Utilizing these lines, we investigated transcriptional changes in the absence of the functional foxd3 protein at three key stages of neural crest ontogeny (75% epiboly, 5–6ss, and 14–16ss) (Figure 2A).
Figure 2Transcriptional Profiling of foxd3 Mutant NC(A) Experimental strategy for obtaining foxd3 -mutant (yellow) and foxd3 -control (green) NC cells.
…”
Section: Resultsmentioning
confidence: 99%
“…De novo assembly and analysis of the foxd3 -mutant transcriptomes revealed the presence of truncated foxd3 fluorescent fusion transcripts (Figure S3A), encoding only 93 N-terminal amino acids, as shown previously (Hochgreb-Hägele and Bronner, 2013). The truncated N-terminal foxd3 variants are non-functional (Yaklichkin et al., 2007), whereas dominant negative activity is associated with the C terminus regions (Kubic et al., 2015, Zhu et al., 2014). Utilizing these lines, we investigated transcriptional changes in the absence of the functional foxd3 protein at three key stages of neural crest ontogeny (75% epiboly, 5–6ss, and 14–16ss) (Figure 2A).
Figure 2Transcriptional Profiling of foxd3 Mutant NC(A) Experimental strategy for obtaining foxd3 -mutant (yellow) and foxd3 -control (green) NC cells.
…”
Section: Resultsmentioning
confidence: 99%
“…Liu et al 6 showed that the metastasis of melanoma can be inhibited by microRNA (miR)-425, which represses the PI3K-Akt pathway by targeting insulin-like growth factor-1. Kubic et al 7 found that PAX3 (paired box 3) and FOXD3 (forkhead box D3) upregulate CXCR4 (C-X-C motif chemokine receptor 4) expression in melanoma. However, the discovery of these biomarkers still fails to fully explain the mechanisms underlying the growth and metastasis of melanoma.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that PAX3 can drive and activate C-X-C motif chemokine receptor 4 (CXCR4)/MET proto-oncogene receptor tyrosine kinase expression, and may promote melanoma metastasis and rapid tumor growth (15,16). E3 ligase APC/C (Cadherin 1) promotes ubiquitination-mediated PAX3 proteolysis and inhibits the proliferation of melanoma cells and melanoma growth (17).…”
Section: Introductionmentioning
confidence: 99%